Faktor Penentu Keberhasilan Megaproyek Infrastruktur: Studi Kasus 4 PSN di Indonesia - Afrinaldi, Afrinaldi (Jurnal Perencanaan dan Pengembangan Kebijakan, 2025)
This study explores the success factors in infrastructure megaprojects in Indonesia, focusing on four National Strategic Projects (PSN): Yogyakarta International Airport, MRT Jakarta, Smelter Morowali, and LRT Palembang. The research uses a multiple case study approach and qualitative analysis to assess the success of the projects based on three key elements: a clear vision, total alignment, and adaptation to complexity. The results indicate that Yogyakarta International Airport achieved the highest score due to its success in all three elements, while the other projects faced significant challenges, particularly in alignment and adaptation to social and environmental challenges. MRT Jakarta Phase 1 and Smelter Morowali were somewhat successful despite challenges such as land acquisition and cost increases, while LRT Palembang faced issues with transport integration and financial sustainability. The key success factors identified in these megaprojects include clear project vision, alignment between strategic, operational, and tactical goals at all stakeholder levels, the ability to address technical, social, and environmental challenges, management transparency, infrastructure integration, and community participation. Based on these findings, the study recommends improving communication and community involvement from the planning stage through to implementation, as well as adopting a more holistic adaptive approach to address social and environmental challenges, aiming to enhance project sustainability and ensure benefits are shared equitably by the community.